0,8 + 3,52 x1.25 -0,52 x0,2x5=(0,8x1,25)+(3,52-0,52)x(0,2x5)
=1+3x1=1+3=4
Đúng 0
Bình luận (0)
0,8 + 3,52 x 1,25 - 0,52 x 0,2 x 5
=0,8 + (3 + 0,52) x 1,25 - 0,52 x (0,2 x 5)
=0,8 + (3 + 0,52) x 1,25 - 0,52 x 1
=0,8 + 3 x 1,25 + 0,52 x 1,25 - 0,52
=0,8 + 3 x 1,25 + 0,52 x (1,25 - 1)
=0,8 + 3 x 1,25 + 0,52 x 0,25
=0,8 + 3 x (1 + 0,25) + 0,52 x 0,25
=0,8 + 3 x 1 + 3 x 0,25 + 0,52 x 0,25
=0,8 + 3 + 0,25 x (3 + 0,52)
=0,8 + 3 + 0,25 x 3,52
=3,8 + 0,25 x 3,52
=15,2 x 0,25 + 0,25 x 3,52
=0,25 x (15,2 + 3,52)
=0,25 x 18,72
=18,72 : 4
=46,8
Đúng 0
Bình luận (0)